Competitividade das exportações de proteína animal do Brasil e sua relação com a sustentabilidade - Binotti, Francieli (2022)
The Brazilian market for animal protein stands out in exports for presenting competitive advantages in the international market and its relationship with sustainability has become an essential point to maintain the competitiveness of the sector. Therefore, the general objective of this research was to analyze the impact of sustainability on the competitiveness of exports of the Brazilian animal protein market (chicken, beef and pork), in the period from 2000 to 2021. if the Constant Market Share (CMS) method, dividing the analysis into sub-periods. The country's sustainability was assessed by social performance, using the Human Development Index (HDI) and by Environmental Performance, assessed from the Genuine Net Savings (ANS). Data collection was carried out through documents available in public institutions, such as the Ministry of Development, Industry and Foreign Trade (MDIC), Secretariat of Foreign Trade (SECEX), World Trade Organization (WTO) and also in the World database. dataBank from the World Bank and UNdata from the UN. The results show that Brazil is competitive in the international animal protein market and has been increasing its share over the years, standing out as an important food supplier to the world. With the arrival of the pandemic in 2020, a reduction in Brazilian exports was expected, due to increased restrictions to combat the Coronavirus, but exports of beef and pork were not affected, only chicken meat had a reduction, in 2020, in the value exported and which was surpassed in the following year. The environmental and social dimensions did not show great influence on competitive performance; factors such as world growth, export destinations and trade barriers exerted greater influence on the country's export performance. Tariff and non-tariff barriers act as a barrier to the expansion of the sector, therefore, there is a need for flexibility agreements to improve policies to encourage competitiveness.